Meta-Analysis of Paclitaxel-Based Chemotherapy Combined With Traditional Chinese Medicines for Gastric Cancer Treatment - Li, Yicong; Sui, Xinbing; Su, Zeqi; Yu, Chunyue; Shi, Xiaoguang; Johnson, Nadia L.; Chu, Fuhao; Li, Yuan; Li, Kexin; Ding, Xia (Frontiers in Pharmacology, 2020)
This study aimed to compare the efficacy and safety of traditional Chinese medicines (TCMs) combined with paclitaxel-based chemotherapy and paclitaxel-based chemotherapy alone for gastric cancer treatment. Literature searches (up to September 25, 2019) were performed using the Cochrane Library, EMBASE, PubMed, Chinese Science and Technology Journals (CQVIP), Wanfang, and China Academic Journals (CNKI) databases. Data from 14 randomized controlled trials (RCTs), with 1,109 participants, were included. The results indicated that, compared with paclitaxel-based chemotherapy alone, the combination of TCMs and paclitaxel-based chemotherapy significantly improved the tumor response rate (TRR; RR: 1.39; 95% CI: 1.24-1.57; p<0.001, I2=12%), increased the quality of life based on the Karnofsky Performance Scale score (RR: 1.53; 95% CI: 1.19-1.96; p<0.001, I2=0%), and reduced the side effects, such as neutropenia (RR: 0.68; 95% CI: 0.55-0.84; p<0.001, I2=44%), leukopenia (RR: 0.69; 95% CI: 0.54-0.90; p<0.01, I2=40%), thrombocytopenia (RR: 0.66; 95% CI: 0.46-0.96; p<0.05, I2=32%), and nausea and vomiting (RR: 0.50; 95% CI: 0.32-0.80; p<0.001, I2=85%). Hepatic dysfunction (RR: 0.63; 95% CI: 0.33-1.20; p=0.16, I2=0%), neurotoxicity (RR: 0.64; 95% CI: 0.26-1.55; p=0.32, I2=0%), and anemia (RR: 0.65; 95% CI: 0.40-1.04; p=0.07, I2=40%) were similar between the two groups. Evidence from the meta-analysis suggested that compared with paclitaxel-based chemotherapy alone, the combination of TCMs and paclitaxel-based chemotherapy may increase the TRR, improve quality of life, and reduce multiple chemotherapy-related side effects in gastric cancer patients. Additional rigorously designed large RCTs are required to confirm the efficacy and safety of this treatment.